Detection of Pneumocystis jirovecii from Clinical Specimens Utilizing a TaqMan‐Based Real‐Time PCR Assay on the Luminex ARIES. Issue 4 (5th April 2021) - Albulushi, Kyle; Jung‐Hynes, Brittney; Chen, Derrick
Abstract: Pneumocystis jirovecii can cause severe pneumonia in immunocompromised patients, which can be life threatening if left untreated. Despite the widespread use of polymerase chain reaction (PCR) within the clinical laboratory setting, FDA‐approved PCR assays are not readily available for the detection of Pneumocystis from respiratory samples. Using the Luminex ARIES system—an open‐channel, automated, sample‐to‐answer PCR platform—the cell division cycle 2 ( cdc‐2 ) gene can be targeted for the detection of Pneumocystis. This novel TaqMan‐based, real‐time PCR assay offers improved sensitivity compared to staining or immunofluorescence while reducing turnaround time and eliminating the challenges surrounding microscopic identification. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Primer/probe master mix preparation Basic Protocol 2 : Positive control ( cdc‐2 ) plasmid preparation Basic Protocol 3 : Mucus digestion Basic Protocol 4 : Cell lysis Basic Protocol 5 : Carrier RNA/proteinase K preparation Basic Protocol 6 : Cassette assembly Basic Protocol 7 : Running the assay Basic Protocol 8 : Interpreting results